LABORATORY DIAGNOSIS OF HEPATITIS B - Haneetha Yogarajah; AA Wiradewi Lestari; IWP Sutirta Yasa (Faculty of Medicine, Udayana University, 2013)
Hepatitis B is a liver disease caused by a virus known as Hepatitis B virus (HBV) and is a major global health probelm. The liver is susceptible to a wide variety of adverse effects caused by an excess of alcohol, drugs, infections such as viral health department. Vaccination for children, adolescents and high-risk adults could also prevent hepatitis B. The prognosis is variable hepatitis, cancer and other metabolic disorders. Hepatitis B is the causative agent and belongs to the hepadnaviridae family of viruses. Transmission of HBV virus is through exposure to infected blood and body fluids. One of the important diagnostic criteria of Hepatitis B is by performing a thorough laboratory investigation.